Changes in Physical Fitness Parameters with Increasing Age - Nevin A. Güzel; Nihan Kafa; Elif Aygun Polat; Ali Zorlular; Çağatay Müslüm Gökdoğan; Esedullah Akaras; Sinem Suner-keklik; Gamze Çobanoğlu (Atatürk University, 2024)
It is inevitable to see changes in physical fitness parameters with age. This study compares the physical fitness parameters, body composition, laxity, balance, proprioception, and muscle strength between different age groups. The study comprised 44 individuals in good health, divided into two age groups: 20-39 and 40-65.Body composition was measured with Tanita BC 418; balance was measured with a Biodex Biosway stabilometer device, and laxity was measured with a GNRB knee arthrometer. The isokinetic system (Cybex NORM, Humac, CA, USA) was used for strength and proprioception measurements. Anteroposterior, mediolateral, and overall stability index among the balance parameters between the two groups was significant. Among the groups, a statistically significant difference was observed in terms of body mass index (BMI), total body fat ratio, trunk fat ratio, and dominant leg fat ratio (p <0.05). It was determined that individuals between the ages of 40-65 had higher BMI, total body fat ratio, trunk fat ratio, and dominant leg fat ratio compared to individuals between the ages of 20-39 and their postural stability was worse. There was no difference between the groups regarding laxity, proprioception, and muscle strength (p> 0.05).With increasing age, it is essential to be aware of the negatively changing body composition and deteriorating balance and encourage participation in physical activity and exercise to prevent physical fitness loss, especially from 40.